2018
DOI: 10.1245/s10434-018-6592-5
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation in Performance for Commission on Cancer Breast Quality Measures and Impact on Overall Survival

Abstract: There is significant regional variation in performance on the breast quality measures but this variation did not impact OS. Targeted efforts in certain areas of the country may help improve performance on these measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…A study of high- versus low-performing regions in the US National Cancer Database did not show differences in survival. 29 However, even low-performing regions provided > 80% concordant care, and variation was slight. Stronger associations with survival might be observed in health care systems with poorer baseline performance and less access to advanced treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A study of high- versus low-performing regions in the US National Cancer Database did not show differences in survival. 29 However, even low-performing regions provided > 80% concordant care, and variation was slight. Stronger associations with survival might be observed in health care systems with poorer baseline performance and less access to advanced treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty-seven papers were selected for full-text review; 64 from the electronic databases and three were selected from the reference list of an earlier systematic review [24]. Of these, 16 papers met the study eligibility criteria [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The stages of the study selection are presented in Figure 1.…”
Section: Included Studiesmentioning
confidence: 99%
“…The National Cancer Database showed that between 2014 and 2015, 305,391 women under 70 years of age underwent surgery as a treatment for breast cancer in the United States [5,6]. The most common breast reconstruction technique to date consists of using a 2-stage tissue expander/implant [7].…”
Section: Introductionmentioning
confidence: 99%